ISOTOPIC ANOMALIES IN CP STARS - Aret, A.; Sapar, A. (Одеські астрономічні публікації, 2017)
In the present paper we analyze the anomalies in the atmospheres of HgMn stars. The abundance anomalies include both overabundances and underabundances of heavy elements. Recent observations show strongly anomalous isotopic composition of Hg, Pt, Tl and of He. Generation of abundance anomalies in quiescent atmospheres of CP stars is successfully explained by the mechanism of diffusional segregation of elements due to oppositing gravitational and radiative forces, but the formation of isotopic anomalies is not yet well explained. New diffusion mechanism called light-induced drift (LID), added to the one of radiative acceleration, successfully explains the observed isotopic anomalies. We have refined the theory of LID and applied it to CP star atmospheres. The results of computations confirm the important role of LID for diffusive segregation of isotopes.